Leveraging Information Technology for Islamic Education Evaluation in the Industry 4.0 Era - Permana, Angga; Maslani, Maslani (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
This study aims to explore the utilization of information technology in Islamic Education (PAI) learning and evaluation, as well as the supporting and hindering factors. A field research approach was used, gathering both secondary and primary data. The results indicate that information technology has been utilized in PAI learning at SD Negeri Bakti through platforms such as Google Meet, Zoom, and WhatsApp when in-class learning is not possible. For evaluation, applications like Quizizz and Google Classroom have been implemented. The school principal supports the use of ICT in teaching and encourages improving competencies through the Merdeka Mengajar platform. However, challenges include some students lacking mobile phones, difficulties faced by teachers in using ICT, inadequate infrastructure, and limited Wi-Fi access due to high user traffic. These findings highlight both the potential and the obstacles in integrating technology into PAI education.